Pengaruh Optimisme Terhadap Stres Akademik Pada Mahasiswa Yang Sedang Mengerjakan Skripsi - Sri Cahya Kencana; Ferdy Muzzamil (Peneliti.net, 2022)
This study was funding the effect of optimism on the academic stress for students who are working on their thesis. The population for this research is students of Bhayangkara University, Jakarta Raya who are working on a thesis with total 2143 people. The sampling technique used in this study was purposive sampling with a research sample of 339 subjects use Slovin formula.. The analysis of the data used is simple linier regression. The results of the ANOVA test obtained an F value of 273.679 with a significance value of 0.001 (p <0.01) which means that there is an effect optimism on the academic stress for students who are working on their thesis.